KOMPOSISI BOTANI DAN PRODUKSI BIOMASSA TANAMAN PAKAN TERNAK DI DESA PONGKOR KABUTAPEN MANGGARAI - Hilarius Yosef Sikone; Erminia Pereira Dos Santos; Yohanes Monterio Kantur; Serlin Anjelita Djami; Albertus Agung; Redemta Hernitania Oktolanung (LPPM UNIVERSITAS KAHURIPAN KEDIRI, 2024)
This study aims to identify the botany of animal feed crops and calculate the biomass production of animal feed crops in the field. The research was conducted in Pongkor Village, Satar Mese District, Manggarai Regency in April-May 2024. The methods used are survey methods as well as measurements and direct observations in the field. Forage production measurements were carried out using the